2023
DOI: 10.1111/cns.14140
|View full text |Cite
|
Sign up to set email alerts
|

In silico and in vitro analyses of a novel FoxO1 agonist reducing Aβ levels via downregulation of BACE1

Abstract: AimsFoxO1 is an important target in the treatment of Alzheimer's disease (AD). However, FoxO1‐specific agonists and their effects on AD have not yet been reported. This study aimed to identify small molecules that upregulate the activity of FoxO1 to attenuate the symptoms of AD.MethodsFoxO1 agonists were identified by in silico screening and molecular dynamics simulation. Western blotting and reverse transcription‐quantitative polymerase chain reaction assays were used to assess protein and gene expression lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Furthermore, increased FoxO1 has been shown to reduce pathological AD features such as tau hyperphosphorylation and amyloid beta (Aβ) plaques ( 190 , 194 196 ). A recent study screened FoxO1 activators as potential therapeutics and demonstrated that one, Compound D, decreases Aβ1-40 and Aβ1-42 in SH-SY5Y cells ( 197 ). Additionally, exercise, an AD intervention, increases circulating FoxO1 in African American men with mild cognitive impairment ( 198 ), and upregulates FoxO1 to improve AD symptoms in early-onset AD mice ( 199 ).…”
Section: Foxo1 and T2d – Brainmentioning
confidence: 99%
“…Furthermore, increased FoxO1 has been shown to reduce pathological AD features such as tau hyperphosphorylation and amyloid beta (Aβ) plaques ( 190 , 194 196 ). A recent study screened FoxO1 activators as potential therapeutics and demonstrated that one, Compound D, decreases Aβ1-40 and Aβ1-42 in SH-SY5Y cells ( 197 ). Additionally, exercise, an AD intervention, increases circulating FoxO1 in African American men with mild cognitive impairment ( 198 ), and upregulates FoxO1 to improve AD symptoms in early-onset AD mice ( 199 ).…”
Section: Foxo1 and T2d – Brainmentioning
confidence: 99%